Uso de plantas medicinais em comunidades de Cuba e Bahia (Brasil) - Hernández, Misleidy Gato (2024)
As part of the history and cultures of Brazil and Cuba, medicinal plants constitute a common community that must be protected for our future generations. Meanwhile, misinformation contributes to the indiscriminate use of medicinal plants in the context of self-medication, demanding studies on their constituents, the mechanism of therapeutic action and the identification of two active principles responsible for the various biological activities reported by the population. For this research, two scientific studies were developed, in the form of scientific articles: a bibliometric study and a case study. The bibliometric study focuses on scientific production related to Cuba and the state of Bahia, in which both present health policies focused on the use of medicinal plants. During the bibliometric study, only one active program was identified in the state of Bahia, in the context of integrative practices and use of medicinal plants in the Unified Health System: Farmácia Viva program in the city of Quijingue, becoming this case study in our case. . As a result of the first study, Bahia exhibited its great diversity of medicinal plants with 136 and 111 in Cuba, despite fewer publications or respect in comparison with Cuba. The pages contain the most used parts of the medicinal plants and the respiratory diseases most treated as well as the Lamiaceae family, which was the most popular. No case study was recommended or use of a new species of Valeriana in substitution of Valeriana officinalis because from the modeling it was demonstrated that V. officinalis would not survive in the climate of Quijingue. It is worth highlighting that this type of research broadens the knowledge and respects the medicinal use of plants, reinforcing traditional knowledge and improving the chances of curing diseases for people; The same way or use of the modeling provides a methodology that allows optimizing the adequação of the species in the projects of the living pharmacy